One‐Step Template‐Free Laser Patterning of Metal Microhoneycomb Structures. Issue 5 (7th April 2022) - Hwang, June Sik; Arthanari, Srinivasan; Park, Jong‐Eun; Yang, Minyang; Kim, Sanha; Kim, Seung‐Woo; Lee, Huseung; Kim, Young‐Jin
Abstract: Metal microhoneycomb structures have received considerable attention as a type of interaction‐efficient functional devices owing to their unique morphology and material properties. Microhoneycomb structures are mainly fabricated using the well‐known breath‐figure method. However, additional post‐treatments are required to produce a metal structure because it is a polymer‐based process, and this necessitates expensive, complex, and multi‐step fabrication processes. Therefore, a simple, low‐cost metal honeycomb fabrication process is necessary. In this paper, the laser patterning of an organometallic solution to produce silver microhoneycomb (Ag microhoneycomb) structures is proposed. Various phenomena such as rapid organic evaporation, silver nanoparticle solidification, and material reorganization from Marangoni flow are found to enable patterning‐induced microhoneycomb formation. Parametric studies demonstrate that the pore size can be easily controlled through simple laser parameter changes. In addition, cyclic voltammetry and electrochemical impedance spectroscopy studies confirm the potential electrochemical applications of the Ag microhoneycomb structures based on the variation of electrochemical redox behavior depending on the pore size. Owing to the excellent advantages of one‐step laser patterning without any templates, the proposed process will likely promote the practical use of the metal microhoneycomb structures. Abstract : The laser patterning of an organometallic solution to produce silver microhoneycomb structures is proposed. Various phenomena such as rapid organic evaporation, silver nanoparticle solidification, and material reorganization from Marangoni flow are found to enable microhoneycomb formation. Parametric studies show the controllability of micropores from simple laser parameter adjustments. The fabricated structures are expected to be the potential electrochemical applications.